The Dilemma of Good Governance Implementation in Indonesia during the Pandemic of Corona Virus Disease (COVID-19) - Haitami, Muzakir; Rengganis, Alya (LPPM Universitas Lampung, 2021)
The Indonesian government's policies to prevent and encounter the spread of Corona Virus Disease (COVID 19) pandemic are still considered not optimal to realize good governance, with the high number of COVID-19 spread throughout Indonesia. This research discusses the implementation of good governance in Indonesia in the COVID-19 pandemic based on eight good governance indicators. This research uses observation techniques to collect the data. The research results indicate that Indonesia is not achieving the ideal target in implementing good governance in overcoming this pandemic. This happened due to a lack of assertiveness in policymaking and a low level of public participation in policy implementation, which led to delays in COVID-19 countermeasures actions. The implementation of policies in China, New Zealand and Turkey indicates that these three countries have the authority to regulate strictly. Meanwhile, in Indonesia, the rule of law and government policies' effectiveness is still weak; delayed action from the government in responding to pandemic proves a lack of government responsiveness. The policies implemented are not based on consensus; equity in accessing public services also becomes a problem. In the end, people lose their trust in the government because they failed to provide unaccountable information. Thus, good governance in Indonesia in the COVID-19 pandemic is still difficult to implement.